Cluster Concept in Enhancing the Marketing Capability of Light Engineering Industry of Bangladesh: A Comparative Study - Forkan, Golam Mohammad (Asian Business Review, 2012)
Though the Light Engineering industry occupies an important space within the Bangladeshi industrial domain, very few attempts of scholarly work to understand and improve the capabilities of this sub-sector has been undertaken in the past. Most of these problems of the sector can be grouped into two fronts: technological deficiencies and marketing inefficiencies. The technological deficiencies are outside the purview of this research, while the marketing challenges are at the center of the research. The objective of this research is to compare perception of different groups of light engineering small enterprises to enhancement of marketing capability through cluster concept. As per the methodology, the first stage of this research comprised of an exploratory research component. The second stage of this research was a conclusive research, where the insights gained from exploratory research were verified. Sampling technique was quota sampling under non-probability sampling. Sample size was 60 representing all the groups. ANOVA test was used to compare perception of different groups of light engineering small businesses. After analysis of variance and F test of all the questions for groups from three dimensions, it was found that perception to enhancement of marketing capability through cluster concept of groups from two dimensions (assets value and number of employee) is positive and variation is also insignificant, i.e., most of the hypotheses are null. Overall perception of groups from another dimension (type of activity) is also positive but variation is significant, i.e., two third hypotheses are null and one third hypotheses are alternative.